A solid agglomerated desiccant and preparation method thereof
A solid agglomerated desiccant with a stable micro-framework structure addresses high moisture absorption and halogen return issues, improving moisture absorption rates and enabling paper packaging for environmental safety.
Patent Information
- Application Number
- CN202411397029.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing magnesium chloride/magnesium oxide desiccants suffer from high moisture absorption rates and the 'sweat wet' phenomenon, leading to halogen return and environmental risks due to plastic packaging, limiting their application prospects.
A solid agglomerated desiccant composed of anhydrous magnesium chloride, magnesium oxide, covalent organic framework material, and additives forms a stable micro-framework structure that absorbs moisture without gelation, using a specific mass ratio of aliphatic and aromatic organic materials to enhance structural stability and adsorption performance.
The desiccant achieves a high moisture absorption rate while maintaining a dry block structure, eliminating halogen return and allowing for paper packaging, thus enhancing safety and environmental performance.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of desiccants, and in particular to a solid agglomerated desiccant and a preparation method thereof. Background Art
[0002] Desiccant is widely used in food, medicine, industrial products, transportation and other industries to ensure that items remain relatively dry during storage and transportation. Desiccant can be divided into two categories according to the principle of moisture absorption: physical hygroscopic type and chemical hygroscopic type. Physical hygroscopic desiccant mainly includes silica gel, mineral desiccant, etc., while chemical hygroscopic desiccant is mainly chloride desiccant, such as calcium chloride and magnesium chloride desiccant, which play an important role in different fields. Regarding chemical hygroscopic desiccant, calcium chloride desiccant on the market is turned into gel after adding starch to absorb moisture, and is mainly used in clothing and footwear, large furniture, electronic equipment and container transportation. Magnesium chloride desiccant adds magnesium oxide and forms a block after absorbing moisture, but there is a "sweat wet" phenomenon, that is, the surface returns to form chloride solution after absorbing moisture, which increases the risk of leakage.
[0003] In order to reduce the moisture absorption and halogen return problem of magnesium chloride / magnesium oxide desiccant, the commonly used solution at present is to add water-resistant admixtures to reduce surface moisture absorption and halogen return. Although it can alleviate the halogen return problem to a certain extent, the moisture absorption rate is not improved, which affects the application prospects of the desiccant. Summary of the invention
[0004] In order to reduce the moisture absorption and halogen return of the desiccant, and at the same time improve the moisture absorption rate, the present application provides a solid agglomerated desiccant and a preparation method thereof.
[0005] In a first aspect, a solid agglomerated desiccant provided in the present application adopts the following technical solution.
[0006] A solid agglomerated desiccant comprises the following raw materials in parts by weight:
[0007] 30-40 parts of anhydrous magnesium chloride;
[0008] 40-50 parts of magnesium oxide;
[0009] 10~20 parts of additives;
[0010] 10-20 parts of covalent organic framework material;
[0011] The covalent organic framework material is obtained by polymerizing aliphatic dihydrazide, aromatic dialdehyde and aromatic dianhydride to obtain a primary framework material, and then by catalytic reaction of the primary framework material, aliphatic monoanhydride and unsaturated higher fatty acid ester.
[0012] By adopting the above technical scheme, anhydrous magnesium chloride and magnesium oxide can form a magnesium oxychloride gelling system with water, so that the desiccant has both moisture absorption and moisture control capabilities, and the additive plays the role of auxiliary moisture absorption and water lock and filler. The covalent organic framework material is a crystalline porous framework with strong covalent forces between the frameworks. A stable micro-framework structure can be formed in the desiccant, which can provide efficient adsorption channels and attachment beds for water molecules, effectively absorb moisture and form water clusters, and is tightly combined with the magnesium chloride / magnesium oxide system and the additive to form a strong cohesive force. After moisture absorption, it presents a dry block structure without melting water or forming a gel, thereby greatly improving the moisture absorption rate of the desiccant while not causing the phenomenon of "returning to halogen". The desiccant is completely dry as a whole. Therefore, the desiccant can be packaged using paper packaging materials, getting rid of the environmental problems caused by the existing chloride desiccant using plastic packaging materials, completely deplasticizing, and conforming to the trend of environmental protection.
[0013] Organic raw materials containing binary reaction functional groups are connected together by covalent bonds, and aliphatic and aromatic organic raw materials are added to improve the rigidity and strength of the material pores. The primary skeleton material is then combined by the reaction of aliphatic monoanhydride and unsaturated higher fatty acid ester, so that the covalent organic skeleton material has a more stable structural characteristic and a higher specific surface area, which helps to improve the moisture absorption rate of the desiccant and ensure the overall block structure of the desiccant. Further, the mass ratio of the aliphatic dihydrazide, aromatic dialdehyde and aromatic dianhydride is (40~50):(30~60):(20~50), and the mass ratio of the primary skeleton material, aliphatic monoanhydride and unsaturated higher fatty acid ester is (10~20):(10~20):(80~100).
[0014] By adopting the above technical solution, the raw materials in the covalent organic framework material adopt a reasonable mass ratio, which further improves the structural stability and adsorption performance of the covalent organic framework material, thereby improving the overall moisture absorption effect and agglomeration stability of the desiccant.
[0015] Furthermore, the raw materials for preparing the covalent organic framework material also include a pH regulator and a catalyst. The pH regulator is used for polymerization reaction and is selected from acetic acid. The catalyst is used for catalytic reaction and is selected from yttrium nitrate.
[0016] Further, the aliphatic dihydrazide is selected from one or more of oxalylhydrazide, malonic acid hydrazide, and succinic acid hydrazide; the aromatic dialdehyde is selected from one or more of terephthalaldehyde, difluoroterephthalaldehyde, and tetrafluorobenzaldehyde; the aromatic dianhydride is selected from one or more of pyromellitic anhydride and biphenyltetracarboxylic anhydride; the aliphatic monoanhydride is selected from one or more of succinic anhydride, glutaric anhydride, and adipic anhydride; the unsaturated higher fatty acid ester is selected from one or more of methyl oleate, ethyl oleate, methyl linoleate, and ethyl linoleate. By adopting the above technical scheme, the specific selection of aliphatic dihydrazide, aromatic dialdehyde, aromatic dianhydride, aliphatic monoanhydride and unsaturated higher fatty acid ester further enhances the hygroscopic performance and overall agglomeration strength of the desiccant, ensures that the desiccant still maintains a dry block shape after absorbing moisture, and improves its application range and environmental performance. Further, the purity of the anhydrous magnesium chloride is 98% or above. By adopting the above technical solution, the high purity of anhydrous magnesium chloride is ensured, thereby improving the hygroscopic performance of the desiccant. Further, the magnesium oxide is active magnesium oxide, and the activity value of the active magnesium oxide is greater than or equal to 150. By adopting the above technical solution, the active magnesium oxide with an activity value greater than or equal to 150 has a high ability to adsorb water and is suitable for desiccant. Further, the additive is selected from one or more of zeolite, vermiculite, white carbon black, super absorbent resin, polyvinyl alcohol, and sodium carboxymethyl cellulose. By adopting the above technical solution, zeolite, vermiculite, white carbon black, super absorbent resin, PVA, and sodium carboxymethyl cellulose all have water absorption capacity, can assist in moisture absorption and water lock, and provide a stable filler effect, ensuring that the desiccant forms a dry block structure after moisture absorption, avoiding gelation and water seepage.
[0017] In a second aspect, the present application provides a method for preparing a solid agglomerated desiccant using the following technical solution.
[0018] A method for preparing a solid agglomerated desiccant comprises the following steps:
[0019] The aliphatic dihydrazide, aromatic dialdehyde, aromatic dianhydride, organic solvent and pH adjuster are mixed in a reaction container, and then an inert gas is introduced into the reaction container to seal the container, and then the polymerization reaction is carried out by heating. After the reaction is completed, the product is filtered, washed and dried to obtain a primary skeleton material;
[0020] The primary framework material, aliphatic monoanhydride, unsaturated higher fatty acid ester and catalyst are added into water, mixed evenly and heated for catalytic reaction, and after the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material;
[0021] Anhydrous magnesium chloride, magnesium oxide, additives and covalent organic framework materials are mixed and stirred to obtain a powder product, which is then extruded and granulated to obtain a solid agglomerated desiccant. By adopting the above technical scheme, the primary framework material is first reacted to obtain the primary framework material, and then the covalent organic framework material is made to have good structural characteristics and high specific surface area through the reaction of aliphatic monoanhydride and unsaturated higher fatty acid ester. The obtained desiccant not only has a high moisture absorption rate, but also can form a stable block structure, and remains dry after moisture absorption, thereby improving the safety and environmental performance of the desiccant.
[0022] Furthermore, before the polymerization reaction, the reaction container is placed in an ultrasonic environment for ultrasonic mixing.
[0023] Furthermore, the polymerization reaction is carried out at 120-150° C. for 40-56 hours.
[0024] Furthermore, the catalytic reaction is carried out at 70-80°C for 2-3h.
[0025] In summary, this application has the following beneficial effects:
[0026] 1. The present application adds a covalent organic framework material to the magnesium chloride / magnesium oxide desiccant. The covalent organic framework material is a crystalline porous framework with strong covalent forces between the frameworks. A stable micro-framework structure can be formed in the desiccant, which can provide efficient adsorption channels and attachment frames for water molecules, effectively adsorb moisture and form water clusters, and tightly combine with the magnesium chloride / magnesium oxide system and additives to form a strong cohesive force. After absorbing moisture, it presents a dry block structure without melting water or forming a gel, thereby greatly improving the moisture absorption rate of the desiccant while not causing the phenomenon of "halogen back". The desiccant is completely dry as a whole. Therefore, the desiccant can be packaged using paper packaging materials, getting rid of the environmental problems caused by the use of plastic packaging materials for existing chloride desiccant, completely deplasticizing, and complying with the trend of environmental protection.
[0027] 2. The primary framework material is combined through the reaction of aliphatic monoanhydride and unsaturated higher fatty acid ester, so that the covalent organic framework material has more stable structural characteristics and higher specific surface area, which helps to improve the moisture absorption rate of the desiccant and ensure the overall block structure of the desiccant. DETAILED DESCRIPTION
[0028] The present application is described in further detail below.
[0029] Example 1
[0030] Preparation of primary skeleton material:
[0031] Weigh 40 g of aliphatic dihydrazide, 30 g of aromatic dialdehyde, 20 g of aromatic dianhydride, and 750 g of an organic solvent.
[0032] The aliphatic dihydrazide is specifically malonic dihydrazide, the aromatic dialdehyde is specifically tetrafluorobenzaldehyde, the aromatic dianhydride is specifically pyromellitic dianhydride, the organic solvent is N,N-dimethylformamide, and the pH adjuster is 5 mol / L acetic acid solution.
[0033] Mix malonic acid hydrazide, tetrafluorobenzaldehyde, pyromellitic anhydride and N,N-dimethylformamide in a reaction container, add acetic acid solution to adjust the pH of the reaction system to 5, place the reaction container in an ultrasonic bath for 10 minutes, then introduce nitrogen into the reaction container to seal it, and perform polymerization at 120°C for 56 hours. After the reaction is completed, filter, wash and dry the product to obtain a primary skeleton material.
[0034] Preparation of covalent organic framework materials:
[0035] Weigh 10 g of primary skeleton material, 10 g of aliphatic monoacid anhydride, 80 g of unsaturated higher fatty acid ester, 0.5 g of catalyst, and 700 g of water.
[0036] The aliphatic monoanhydride is specifically succinic anhydride, the unsaturated higher fatty acid ester is specifically methyl oleate, and the catalyst is specifically yttrium nitrate.
[0037] The primary framework material, succinic anhydride, methyl oleate and yttrium nitrate are added into water, mixed evenly and then catalytically reacted at 70°C for 2 hours. After the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material.
[0038] Preparation of solid agglomerated desiccant:
[0039] Weigh 30 g of anhydrous magnesium chloride, 40 g of magnesium oxide, 10 g of additives, and 10 g of covalent organic framework material.
[0040] The purity of anhydrous magnesium chloride is 98%, the magnesium oxide is specifically activated magnesium oxide, the activity value of the activated magnesium oxide is 150, and the additive is specifically zeolite.
[0041] Anhydrous magnesium chloride, active magnesium oxide, additives and covalent organic framework materials are mixed and stirred at a speed of 300 r / min for 0.5 h to obtain a powder product, which is then extruded and granulated to obtain a solid agglomerated desiccant.
[0042] Example 2
[0043] Preparation of primary skeleton material:
[0044] Weigh 40 g of aliphatic dihydrazide, 60 g of aromatic dialdehyde, 50 g of aromatic dianhydride, and 1000 g of an organic solvent.
[0045] The aliphatic dihydrazide is specifically malonic dihydrazide, the aromatic dialdehyde is specifically tetrafluorobenzaldehyde, the aromatic dianhydride is specifically pyromellitic dianhydride, the organic solvent is N,N-dimethylformamide, and the pH adjuster is 5 mol / L acetic acid solution.
[0046] Mix malonic acid hydrazide, tetrafluorobenzaldehyde, pyromellitic anhydride and N,N-dimethylformamide in a reaction container, add acetic acid solution to adjust the pH of the reaction system to 5, place the reaction container in an ultrasonic bath for 10 minutes, then introduce nitrogen into the reaction container to seal it, and perform polymerization at 150°C for 40 hours. After the reaction is completed, filter, wash and dry the product to obtain a primary skeleton material.
[0047] Preparation of covalent organic framework materials:
[0048] Weigh 20 g of primary skeleton material, 20 g of aliphatic monoacid anhydride, 80 g of unsaturated higher fatty acid ester, 1 g of catalyst, and 800 g of water.
[0049] The aliphatic monoanhydride is specifically succinic anhydride, the unsaturated higher fatty acid ester is specifically methyl oleate, and the catalyst is specifically yttrium nitrate.
[0050] The primary framework material, succinic anhydride, methyl oleate and yttrium nitrate are added into water, mixed evenly and then catalytically reacted at 80°C for 3 hours. After the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material.
[0051] Preparation of solid agglomerated desiccant:
[0052] Weigh 40 g of anhydrous magnesium chloride, 50 g of magnesium oxide, 20 g of additives, and 20 g of covalent organic framework material.
[0053] The purity of anhydrous magnesium chloride is 98%, the magnesium oxide is specifically active magnesium oxide, the activity value of the active magnesium oxide is 180, and the additive is specifically white carbon black.
[0054] Anhydrous magnesium chloride, active magnesium oxide, additives and covalent organic framework materials are mixed and stirred at a speed of 300 r / min for 0.5 h to obtain a powder product, which is then extruded and granulated to obtain a solid agglomerated desiccant.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 is that the amount of raw materials used is different.
[0057] In the steps of preparing the primary skeleton material:
[0058] Weigh 45 g of aliphatic dihydrazide, 45 g of aromatic dialdehyde, 35 g of aromatic dianhydride, and 800 g of an organic solvent.
[0059] The aliphatic dihydrazide is specifically malonic dihydrazide, the aromatic dialdehyde is specifically tetrafluorobenzaldehyde, the aromatic dianhydride is specifically pyromellitic dianhydride, the organic solvent is N,N-dimethylformamide, and the pH adjuster is 5 mol / L acetic acid solution.
[0060] In the steps of preparing covalent organic framework materials:
[0061] Weigh 15 g of primary skeleton material, 15 g of aliphatic monoanhydride, 85 g of unsaturated higher fatty acid ester, 0.5 g of catalyst, and 700 g of water.
[0062] The aliphatic monoanhydride is specifically succinic anhydride, the unsaturated higher fatty acid ester is specifically methyl oleate, and the catalyst is specifically yttrium nitrate.
[0063] In the steps of preparing a solid agglomerated desiccant:
[0064] Weigh 35 g of anhydrous magnesium chloride, 45 g of magnesium oxide, 15 g of additives, and 15 g of covalent organic framework material.
[0065] The purity of anhydrous magnesium chloride is 98%, the magnesium oxide is specifically activated magnesium oxide, the activity value of the activated magnesium oxide is 180, and the additive is specifically zeolite.
[0066] Example 4
[0067] The difference between this embodiment and embodiment 3 lies in the different steps of preparing the covalent organic framework material.
[0068] Preparation of covalent organic framework materials:
[0069] Weigh 15 g of the primary skeleton material obtained in Example 3, 85 g of unsaturated higher fatty acid ester, and 700 g of water.
[0070] The unsaturated higher fatty acid ester is specifically methyl oleate.
[0071] The primary framework material and methyl oleate are added into water, mixed evenly and then catalytically reacted at 70° C. for 2 hours. After the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material.
[0072] Example 5
[0073] The difference between this embodiment and embodiment 3 lies in the different steps of preparing the covalent organic framework material.
[0074] Preparation of covalent organic framework materials:
[0075] Weigh 15 g of the primary framework material obtained in Example 3, 15 g of aliphatic monoacid anhydride, 0.5 g of catalyst, and 700 g of water.
[0076] The aliphatic monoanhydride is specifically succinic anhydride, and the catalyst is specifically yttrium nitrate.
[0077] The primary framework material, succinic anhydride and yttrium nitrate are added into water, mixed evenly and then catalytically reacted at 70°C for 2 hours. After the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material.
[0078] Example 6
[0079] The difference between this embodiment and embodiment 3 is that the steps for preparing the primary skeleton material are different.
[0080] Preparation of primary skeleton material:
[0081] Weigh 45 g of aliphatic dihydrazide, 45 g of aliphatic dialdehyde, 35 g of aromatic dianhydride, and 800 g of an organic solvent.
[0082] The aliphatic dihydrazide is specifically malonic dihydrazide, the aliphatic dialdehyde is specifically glutaraldehyde, the aromatic dianhydride is specifically pyromellitic dianhydride, the organic solvent is N,N-dimethylformamide, and the pH adjuster is 5 mol / L acetic acid solution.
[0083] Mix malonic acid hydrazide, glutaraldehyde, pyromellitic acid dianhydride and N,N-dimethylformamide in a reaction container, add acetic acid solution to adjust the pH of the reaction system to 5, place the reaction container in an ultrasonic bath for 10 minutes, then introduce nitrogen into the reaction container to seal it, and perform polymerization at 120°C for 56 hours. After the reaction is completed, filter, wash and dry the product to obtain a primary skeleton material.
[0084] Comparative Example 1
[0085] Preparation of solid agglomerated desiccant:
[0086] Weigh 35 g of anhydrous magnesium chloride, 45 g of magnesium oxide, and 15 g of additives.
[0087] The purity of anhydrous magnesium chloride is 98%, the magnesium oxide is specifically activated magnesium oxide, the activity value of the activated magnesium oxide is 150, and the additive is specifically zeolite.
[0088] Anhydrous magnesium chloride, active magnesium oxide and additives are mixed and stirred at a speed of 300 r / min for 0.5 h to obtain a powder product, which is then extruded and granulated to obtain a solid agglomerated desiccant.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 3 is that the steps for preparing the primary skeleton material are different.
[0091] Preparation of primary skeleton material:
[0092] Weigh 45 g of aliphatic dihydrazide, 45 g of aromatic dialdehyde, and 800 g of an organic solvent.
[0093] The aliphatic dihydrazide is specifically malonic dihydrazide, the aromatic dialdehyde is specifically tetrafluorobenzaldehyde, the organic solvent is N,N-dimethylformamide, and the pH adjuster is 5 mol / L acetic acid solution.
[0094] Mix malonic acid hydrazide, tetrafluorobenzaldehyde and N,N-dimethylformamide in a reaction container, add acetic acid solution to adjust the pH of the reaction system to 5, place the reaction container in an ultrasonic bath for 10 minutes, then introduce nitrogen into the reaction container to seal it, and perform polymerization at 120°C for 56 hours. After the reaction is completed, filter, wash and dry the product to obtain a primary framework material.
[0095] Performance Testing
[0096] Moisture absorption rate detection: Referring to the moisture absorption rate test method in BBT0049-2021 "Desiccant for Packaging", 10g of each solid agglomerated desiccant prepared in Examples 1-6 and Comparative Examples 1-2 was placed in a constant temperature and humidity chamber, and the moisture absorption rate on the third day after the start of the test was calculated. After the desiccant reached adsorption equilibrium, the total moisture absorption rate was calculated. The temperature of the constant temperature and humidity chamber was 25℃±2℃, and the relative humidity was 90%±2%. The test results are shown in Table 1.
[0097] Property observation: observe whether the desiccant that has completed the moisture absorption rate test has any halogen return phenomenon, and divide it into four levels according to the degree of halogen return: level 0, level 1, level 2, and level 3. Level 0 represents no halogen return, and level 3 represents severe halogen return. The results are shown in Table 1.
[0098] Strength test: The compressive strength tester was used to test the desiccant after the moisture absorption reached adsorption equilibrium. The results are shown in Table 1.
[0099] Total moisture absorption rate (%) Three-day moisture absorption rate (%) Brine grade Compressive strength(N) Example 1 326 136 Level 0 20 Example 2 310 132 Level 0 23 Example 3 345 141 Level 0 22 Example 4 266 104 Level 1 18 Example 5 285 110 Level 0 19 Example 6 243 98 Level 1 19 Comparative Example 1 156 82 Level 3 13 Comparative Example 2 202 90 Level 2 16
[0100] Combined with the analysis in Table 1, compared with Comparative Example 1 in which no covalent organic framework material is added, the desiccant prepared in Example 3 has obvious improvements in moisture absorption rate and anti-halogen reversion, which makes up for the defects of traditional magnesium chloride / magnesium oxide desiccant, improves the drying capacity of the desiccant, and has high compressive strength, more applicable scenarios, and is overall dry, can get rid of plastic packaging materials, and has broader application prospects.
[0101] Compared with Comparative Example 2, Example 3 introduces aromatic dianhydride as a cross-linking agent to prepare the primary framework material, thereby preparing a covalent organic framework material with stable structure and strong adsorption and water-locking ability, and is more suitable for application in desiccant.
[0102] By comparing Example 3 with Examples 4-6, it can be found that the use of aliphatic monoanhydride and unsaturated higher fatty acid ester to modify the primary skeleton material can effectively improve the moisture absorption capacity of the desiccant, and the moisture absorption rate is greatly accelerated. The primary skeleton material adopts the covalent combination of aliphatic organic structure and aromatic organic structure, and the ability of moisture absorption and water locking is greatly enhanced.
[0103] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A solid agglomerated desiccant, It is characterized in that The invention comprises the following raw materials in parts by weight: 30-40 parts of anhydrous magnesium chloride; 40-50 parts of magnesium oxide; 10-20 parts of additives; 10-20 parts of covalent organic framework materials; the covalent organic framework materials are obtained by polymerizing aliphatic dihydrazides, aromatic dialdehydes and aromatic dianhydrides to obtain a primary framework material, and then by catalyzing a reaction between the primary framework material, aliphatic monoanhydrides and unsaturated higher fatty acid esters to obtain the product; The mass ratio of the aliphatic dihydrazide, the aromatic dialdehyde and the aromatic dianhydride is (40-50):(30-60):(20-50), and the mass ratio of the primary skeleton material, the aliphatic monoanhydride and the unsaturated higher fatty acid ester is (10-20):(10-20):(80-100); The aliphatic dihydrazide is selected from one or more of oxalylhydrazide, malonic acid hydrazide and succinic acid hydrazide; the aromatic dialdehyde is selected from one or more of terephthalaldehyde, difluoroterephthalaldehyde and tetrafluorobenzaldehyde; the aromatic dianhydride is selected from one or more of pyromellitic acid dianhydride and biphenyltetracarboxylic acid dianhydride; the aliphatic monoanhydride is selected from one or more of succinic anhydride, glutaric anhydride and adipic anhydride; the unsaturated higher fatty acid ester is selected from one or more of methyl oleate, ethyl oleate, methyl linoleate and ethyl linoleate.
2. The solid agglomerating desiccant according to claim 1, It is characterized in that The purity of the anhydrous magnesium chloride is 98% or above.
3. The solid agglomerating desiccant according to claim 1, It is characterized in that The magnesium oxide is active magnesium oxide.
4. The solid agglomerated desiccant according to claim 1, It is characterized in that The additive is selected from one or more of zeolite, vermiculite, white carbon black, super absorbent resin, polyvinyl alcohol, and sodium carboxymethyl cellulose.
5. A method for preparing the solid agglomerated desiccant according to any one of claims 1 to 4, It is characterized in that The following steps are involved: Aliphatic dihydrazide, aromatic dialdehyde, aromatic dianhydride, organic solvent and pH regulator are mixed in a reaction container, and then inert gas is introduced into the reaction container to seal it, and then heating is performed for polymerization reaction. After the reaction is completed, the product is filtered, washed and dried to obtain a primary framework material; The primary framework material, aliphatic monoanhydride, unsaturated higher fatty acid ester and catalyst are added into water, mixed evenly and heated for catalytic reaction. After the reaction is completed, the product is filtered, washed and dried to obtain a covalent organic framework material; Anhydrous magnesium chloride, magnesium oxide, additives and covalent organic framework materials are mixed and stirred to obtain a powder product, and a solid agglomerated desiccant is obtained by extrusion granulation.
6. The method for preparing the solid agglomerated desiccant according to claim 5, It is characterized in that Before the polymerization reaction, the reaction container was placed in an ultrasonic bath for ultrasonic mixing.
Citation Information
Patent Citations
Covalent organic frameworks
CN114981335A
Covalent organic framework material with air water collection performance and preparation method thereof
CN115677954A
Polysalts of acid-ester compounds with hydrazine or hydrazides and method of preparing heterocyclic polymers from said polysalts
US4089846A
Green solid-phase synthesis method for covalent organic framework material
WO2023124952A1
